PENGARUH LAMA PENGADUKAN CAMPURAN BETON TERHADAP KUAT TEKAN BETON - Arif Setyo Wibowo; Ninik Paryati, Fajar Prihesnanto, Anita Setyowati Srigunarti (Jurnal Salome : Multidisipliner Keilmuan, 2024)
The factor that affects the concrete stirring process is the stirring time. Precise concrete stirring time can improve the quality of concrete and its strength. This research will be carried out by conducting concrete testing experiments on certain stirring time variations. The hope of the results of this study is to present information about the right concrete stirring time to create a quality concrete mixture that has strength that meets the standards. The research technique applied is an experimental approach. This study aims to determine the comparison of the compressive strength of normal concrete with concrete substituted in 10 minutes, 20 minutes and 30 minutes, the effect of the time of mixing the concrete mixture on the compressive strength of concrete. The main test is the compressive strength of concrete based on SNI 03- 6825-2002 using a Compression Test Machine with a capacity of 1500 kN with ASTM C-39 test standard. For data processing using Ms. Excel, from the results of the analysis test, it was obtained that the slump value was smaller the longer the stirring and for the compressive strength of concrete at the age of 28 days. The results of the study showed that the longer the stirring the slump value was higher, the thinner the concrete so that it was easier to work with the concrete, the mixture was mixed well so that the printing was perfect and the results were better because there was no segregation (grain separation). The most optimal concrete compressive strength is obtained at a stirring time of 30 minutes with a compressive strength of 20.17 Mpa or an increase of 0.9% from the planned concrete compressive strength.